Building Information Modeling (BIM) Implementation Towards Improving Collaborative Communication in Construction Projects - Leonard Doudilim, Yvonne Valerie; Masrom, Md Asrul Nasid; Ahmad Latiffi, Aryani; Kasim, Narimah (Research in Management of Technology and Business, 2021)
Collaborative communication (CC) in construction projects have become a key issue to be addressed as CC is considered as main factor of project success. Building Information Modeling (BIM) has been recognized as a method to improve CC. However, BIM implementation is challenged by the current practices of traditional CC in construction industry. Objectives of this research are therefore to identify CC issues in the current practices among project participants, to determine the benefits of BIM in improving CC and to assess the potential ways to enhance CC with challenges in BIM implementation for construction projects. Data collection method used is qualitative method, whereas interview was conducted with project participants in Kota Kinabalu, Sabah that are familiar with BIM implementation for CC in construction project. This finding found that all respondents agreed on CC issues that consist of practices of poor CC, non-standardised information sharing, low level of CC, and lack of advance technology support. Respondents agreed that with BIM implementation, it improved CC with better project visualisation, as a single environment platform, integrated CC, and increased productivity of construction projects. Potential ways for BIM implementation are compulsory of BIM implementation in contract document, provide training such as workshops, Webinar, subsidies from Government, promote BIM extensively through BIM implementation in Government project, and investing on technologies tools for online interaction. In conclusion, this research encourages the stakeholders to implement BIM for CC among project participants. Further research should be focus on how to utilize BIM in project management during COVID19 crisis.Collaborative communication (CC) in construction projects have become a key issue to be addressed as CC is considered as main factor of project success. Building Information Modeling (BIM) has been recognized as a method to improve CC. However, BIM implementation is challenged by the current practices of traditional CC in construction industry. Objectives of this research are therefore to identify CC issues in the current practices among project participants, to determine the benefits of BIM in improving CC and to assess the potential ways to enhance CC with challenges in BIM implementation for construction projects. Data collection method used is qualitative method, whereas interview was conducted with project participants in Kota Kinabalu, Sabah that are familiar with BIM implementation for CC in construction project. This finding found that all respondents agreed on CC issues that consist of practices of poor CC, non-standardised information sharing, low level of CC, and lack of advance technology support. Respondents agreed that with BIM implementation, it improved CC with better project visualisation, as a single environment platform, integrated CC, and increased productivity of construction projects. Potential ways for BIM implementation are compulsory of BIM implementation in contract document, provide training such as workshops, Webinar, subsidies from Government, promote BIM extensively through BIM implementation in Government project, and investing on technologies tools for online interaction. In conclusion, this research encourages the stakeholders to implement BIM for CC among project participants. Further research should be focus on how to utilize BIM in project management during COVID19 crisis.